Reconstruction Al-Ghazālī’s Concept of Sa‘Ādah as a Normative Framework for Contemporary Islamic Education - Zainul Rhofik; M. Ramli; Muslihati; Muhammad Naufal Tsabitul Azmy (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This article examines al-Ghazālī’s concept of sa‘ādah in Kīmiyā’ al-Sa‘ādah and reconstructs it as a normative framework for contemporary Islamic education. The study responds to modern educational orientations that increasingly emphasize instrumental, utilitarian, academic, and economic achievement, often at the expense of moral formation, spiritual cultivation, and students’ sense of meaning. Methodologically, this study employed a Systematic Literature Review combined with textual-hermeneutic analysis. The review followed PRISMA 2020 procedures, including database searching, duplicate removal, title and abstract screening, full-text eligibility assessment, inclusion and exclusion criteria, quality appraisal, and thematic synthesis. The primary source was the 2022 edition of Kīmiyā’ al-Sa‘ādah, while the secondary sources consisted of peer-reviewed studies and scholarly works on sa‘ādah, al-qalb, ma‘rifat Allāh, the integration of ‘ilm and ‘amal, mujāhadah, riyāḍah, tazkiyat al-nafs, the role of the murabbī, and contemporary Islamic education. The findings reveal four major themes: sa‘ādah as the teleological aim of education grounded in the perfection of the heart through ma‘rifat Allāh; the integration of knowledge, action, and spiritual striving; the moderation of anger, desire, and knowledge as the basis of virtue formation; and the role of tazkiyah, riyāḍah, and the murabbī in self-formation. The study concludes that al-Ghazālī offers a coherent conceptual basis for reorienting Islamic education toward holistic ethical, spiritual, and intellectual development.